Bibliometric Analysis on Scholarly Journals of PVA Hydrogel Membrane Using VOSviewers Software - Virni Grace Irene Damanik; Asep Bayu Dani Nandiyanto (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
The development of technology in this world is already developing rapidly. One of the advanced technologies that support research planning is bibliometrics. This study aims to analyze the scope of research on PVA Hydrogel Membrane using VOSviewer using bibliometric review with a mapping process to ensure that the research to be carried out has never been studied and knows the relationship of each related item. The three processes underlying the search use the keywords "chemistry, particle, PVA, and Hydrogel" namely title, abstract, and keyword. The research database is taken from google scholar. A total of 98 articles are relevant and meet the criteria. The results show that most of the studies were conducted in the 2012-2022 range. PVA and Hydrogel are so closely related to each other that they have a fairly bright density visualization. Some items are not related to the PVA Hydrogel Membrane but these items are interconnected with other items so it can be concluded that there are still many items that can be used for further research.